Assessment of Overall Thermal Transfer Value (OTTV) in Buildings with Inclined Glass Wall - Sudprasert, Sudaporn; Klinsmith, Sivayu (Journal of Architectural/Planning Research and Studies (JARS), 2014)
The Ministry of Energy of Thailand promulgated the criteria for computing the Overall Thermal Transfer Values (OTTV) to manage building energy efficiency in 1992. These criteria were improved in 2009 to cover dissimilar heat transfer rates in the daytime and the nighttime for offices, stores and hotels constructed with 0 to 90-degree roofs and walls. However, the assessment of OTTV of buildings with wall inclinations greater than 90 degrees has been excluded with only approximate values being used in the calculation. The objective of this paper, therefore, is to propose a calculation method of Effective Solar Radiation (ESR), a variable in OTTV equation, for office buildings with 105-150 degree wall inclinations, taking into account the effects of ground reflectance values of 0.05, 0.2 and 0.32 for water, grass, and white concrete, respectively. The ESR values for the inclined glass wall were obtained from the slope of linear relationship between the simulated solar heat gain and the glass’s Solar Heat Gain Coefficient (SHGC). The simulated results and the regression analysis showed that the derived ESR values of the vertical wall were compatible with the ESR values in the building energy code (BEC) and the energy used index, similar to that obtained from energy audits. The ESR values decreased by 2.7-37% as the glass wall inclination increased, resulting in a decrease of the OTTV by 2.0-17%. For the high ground reflectance of 0.32 and SHGC of 0.54, the results showed that the OTTVs of the building with inclined walls exceeded 50 W/m2. Therefore, grass and water are recommended for the landscape around energy efficient buildings.